PENGARUH PLYOMETRIC EXERCISES TERHADAP EXPLOSIVE POWER OTOT TUNGKAI SAAT MELAKUKAN BLOCKING PADA TIM BOLA VOLI PUTRI SMAN 9 PEKANBARU - Saputra, Prio; ', Slamet; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: from the result of field observasions in mind that there were many shortcomings exercises leads to increased leg muscle explosive power. Based on the existing problems, the researchers aimed to provide a from of exercise that could improve exsplosive power and leg muscles giving intensive training program. In this research the authors only focused on one form of exercises plyometric exercises as a form of exercise has not been tried on women’s volleyball team SMAN 9 pekanbaru. This research used experimental research methods, in order to determine the effect of exercises. This the experimental research method can be interpreted as a method of research that is useful to search for a specific treatment effect against the orther in uncontrolled conditions. The first step taken was doing pre-test with power vertical power jumpt test. Tosee the effect of treatment. Data were analyzed descriptively, then further testing research hypotheses have been proposed to fit the problem is there was the influence of plyometric exercises. Exercises are significant to the explosive power leg muscle while doing the blocking. Based on t test analysis produced T calculated at 6.51 and 1.796 T table. T means the arithmetic > T TABLE. We could conclude that Ha accepted. So it could be summed up as follows: there was the influence of the explosive power of the explosive power of plyometric exercises leg muscles while doing the blocking in the women’s volleyball team SMAN 9 pekanbaru.Keywords : plyometric exercises, muscle power explosive limbs